COPD in Poland – risk factor and epidemiology - Warchoł, Martyna (Journal of Education, Health and Sport, 2018)
Chronic obstructive pulmonary disease (COPD) falls under the category of civilization diseases. According to World Health Organization, its burden is expected to increase in the following decades, mainly due to constant exposition to the risk factors, population growth and ageing, to become the third most frequent cause of death until 2030. According to the guidelines of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) from 2015, COPD can be prevented and successfully treated. Despite the serious problem that is COPD, in many countries the data on this disease is insufficient. The most important risk factor leading to COPD that can be modified is smoking tobacco, the habit that is still popular among the adults. The knowledge of the risk factors and their elimination, as well as leading a healthy lifestyle and preference towards health behaviour that helps reducing the advancement of the disease should therefore become the basis for preventing COPD.